2018
DOI: 10.1002/cpp.2185
|View full text |Cite
|
Sign up to set email alerts
|

A proof‐of‐concept pilot randomized comparative trial of brief Internet‐based compassionate mind training and cognitive‐behavioral therapy for perinatal and intending to become pregnant women

Abstract: These findings provide a compelling initial argument for the use of CMT as an avenue for addressing problems associated with negative affect. Implications, limitations, and future directions along this line of research will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 57 publications
4
73
0
Order By: Relevance
“…These findings indicate that training compassion-based techniques is more effective in reducing the feeling of loneliness and emotional regulation problems in runaway girls than cognitive-behavioral techniques. This result is in line with the findings of Ghaffarians and Khayatan (2018) and Qasemabadi, Khalatbari, Ghorban Shiroudi and Rahmani (2019), Bagean Koulemarz, Karami, Momeni andElahi (2019), Movahedi (2018), Dasht Bozorgi (2018) and Kelman, Evare, Barrera, Muñoz and Gilbert (2018).…”
Section: Discussionsupporting
confidence: 89%
“…These findings indicate that training compassion-based techniques is more effective in reducing the feeling of loneliness and emotional regulation problems in runaway girls than cognitive-behavioral techniques. This result is in line with the findings of Ghaffarians and Khayatan (2018) and Qasemabadi, Khalatbari, Ghorban Shiroudi and Rahmani (2019), Bagean Koulemarz, Karami, Momeni andElahi (2019), Movahedi (2018), Dasht Bozorgi (2018) and Kelman, Evare, Barrera, Muñoz and Gilbert (2018).…”
Section: Discussionsupporting
confidence: 89%
“…[ 78 82 ] Significant reduction ( P < .05) in depression and anxiety was reported in 18 of the included studies which received psychotherapy. [ 52 , 53 , 65 78 , 80 82 ] and three studies reported no effect, [ 50 , 51 , 79 ] of psychotherapy on depression, anxiety and maternal quality of life during the antenatal stage of pregnancy. Qualitative and quantitative data were then extracted from all the studies and summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Those that are available have reported encouraging results. For example, a proof-of-concept study compared a 2-week web-based CBI with web-based cognitive behavioral therapy (CBT) for perinatal women and those planning pregnancy (n=123) [ 52 ]. Participants in the 2 groups had similar outcomes in terms of affect, self-reassurance, self-criticism, and self-compassion.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of potential benefits of delivering MBIs and CBIs via the internet [ 52 , 54 ], such as the capacity to implement across populations, to reach individuals who might struggle to access face-to-face services, the potential to improve cost-efficiencies, and the ability to provide greater flexibility to service users [ 55 ]. Meta-analyses have found small-to-moderate effect sizes for web-based and self-guided MBIs in promoting well-being and reducing symptoms of psychological distress [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation